2H-Pyrrole und Pyrrole aus 3-Phenyl-2H-azirinen - Ulrich Widmer; Nikolas Gakis; Bruno Arnet; Heinz Heimgartner; Hans Schmid (CHIMIA)
Vinyl-phosphonium salts [2] and phenyl-vinyl-sulfone or divinylsulfone react with benzonitril-methylides a (which are photochemically generated from 3-phenyl-2H-azirines 1 and 2) to give, via the nonisolated intermediates of type b, 2H-pyrrole 4 and the pyrrole 5, respectively. In the reaction of sulfone 11 it was shown that the addition reaction occurs with the retention of configuration of the olefin and with the same regioselectivity as observed in the cycloadditions of acrylic ester or acrylic nitrile with a [5]. In the case of 11 the primary photoproduct 13 (scheme 2) could be isolated, which on photolysis was converted to 4 by the formal elimination of p-tosylchloride. Under mild base catalysis, for instance with the azirine 1 as a base, elimination of p-toluenesulfinic acid occurs easily at room temperature to give the 2H-pyrrole 12. Vinyl-phosphonium salts or vinyl-sulfones can be considered equivalents of non activated acetylenes which do not react with a.